P27 Routine Piloting in Systematic Reviews to Improve Usability: A Case Study. (13th September 2016) - Long, L; Abraham, C
Abstract : Background: In 2014, Long proposed a novel methodology for the routine piloting of a systematic review through to evidence synthesis stage using data from a sample of included papers in order to improve efficiency and validity. This paper describes the application of the method in a systematic review that informs a research programme seeking to address the rise in sexually transmitted infections in young people (14–25 yrs) and men who have sex with men (MSM). Methods: A systematic review was conducted to identify RCTs of low intensity interventions suitable for implementation in UK Sexual Health clinics. Seven databases were searched up to October 2014. 23 young people RCTs and 10 MSM RCTs were identified for inclusion. A sample of five young people studies was piloted through to evidence synthesis, undergoing data extraction and quality appraisal using the Cochrane 'risk of bias' tool. Summary tables describing intervention delivery and study outcomes were created and characteristics of interventions and details of participant population were recorded. Following the mini-synthesis, the data extraction form and Summary of Findings tables were circulated to team members in all three participating research institutions and feedback was sought on their usefulness to inform the next stage of the project. MSM papers were not subject to the piloting method and were processed according to traditional systematic review protocol. Results: Following the mini-synthesis, a number of criteria in the data extraction form and Summary of Findings table format were identified as needing modification. Both were amended accordingly. Data from the remaining young people RCTs were efficiently extracted in one phase and a final Summary of Findings table for young people compiled. Ten MSM RCTs were data extracted and quality appraised. However, when the data extraction form and Summary of Findings table format were modified for extraction of relevant data, all ten MSM studies had to be re-visited and a second phase of data extraction performed. Conclusion: Routine piloting in systematic reviews facilitated production of a "bespoke" review, with time saved both through efficient extraction of required data and the avoidance of extraction of unnecessary data. In addition, the mini synthesis provided a potential version of the full review that could be discussed and agreed by all researchers at an early stage in the review process. This supported project management of the review, improved efficiency and ensured optimal usability for the researchers involved in the next stage of the research programme.